Analysis Of Factors Associated with The Use of IUD in Women of Childbearing Age - Kristanti, Yani; Noor , Meitria Syahadatina; Arifin, Syamsul; Ringoringo , Harapan Parlindungan; Hartoyo, Edi (Grimsa Journal of Science Engineering and Technology, 2024)
The Intra-Uterine Device (IUD) stands out as one of the safest long-term contraceptives, boasting a remarkable user effectiveness rate of 99.4%. Despite this, recent data from the 2021 Indonesian health profile in South Kalimantan Province reveals suboptimal coverage of IUD usage. Specifically, the coverage stands at 1.95% with 12,011 users in the region, 1.02% (477 users) in Kotabaru District, and 1.79% (82 users) in the Serongga Health Center. These figures fall short of the targeted coverage of 12.9%. This study aims to identify factors influencing IUD usage among women of childbearing age. Employing an analytical observational method with a Case-Control design, the research was conducted within the Serongga Health Center's jurisdiction. The investigation sought to establish correlations between education, knowledge, occupation, age, parity, and husband support with the utilization of IUDs among women of childbearing age. Utilizing a cluster proportional random sampling technique, the study comprised a sample population of 110 individuals. Statistical analysis involved the application of the Chi-Square test and Logistic Regression test for multivariate analysis. The findings of the study indicate that education (p=0.554), knowledge (p=0.308), age (p=0.566), and parity (p=0.835) demonstrate no significant association with IUD usage among women of childbearing age. Conversely, occupational factors (p=0.022, Exp (B)=2.667) and husband support (p=0.035, Exp (B)=2.813) exhibit a notable association. Notably, occupation emerges as the dominant factor influencing IUD usage.